2013
DOI: 10.12659/aot.889269
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and tolerability of subcutaneous hepatitis B immunoglobulin self-administration in liver transplant patients: A prospective, observational, multicenter study

Abstract: Subcutaneous HBIg home-based self-administration under routine, real-life conditions is well-tolerated and associated with high compliance and maintaining protective anti-HBs serum concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 99 A prospective, observational, 18-week, open-label, single-arm, multicenter study confirmed that self-administering SC HBIG at home achieved high compliance and tolerability in maintenance liver transplant patients. 100 Thürmann et al investigated pharmacokinetics and safety of a novel HBIG (Biotest AG) in healthy volunteers after a single SC or IM dose of 30 IU/kg and observed that the two routes have comparable pharmacokinetic parameters. 101 Biotest AG launched Zutectra ® as a new SC prophylaxis against HBV reinfection in 2010.…”
Section: Resultsmentioning
confidence: 99%
“… 99 A prospective, observational, 18-week, open-label, single-arm, multicenter study confirmed that self-administering SC HBIG at home achieved high compliance and tolerability in maintenance liver transplant patients. 100 Thürmann et al investigated pharmacokinetics and safety of a novel HBIG (Biotest AG) in healthy volunteers after a single SC or IM dose of 30 IU/kg and observed that the two routes have comparable pharmacokinetic parameters. 101 Biotest AG launched Zutectra ® as a new SC prophylaxis against HBV reinfection in 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Higher HBIg dosage is associated with a lower frequency of HBV recurrence even in patients receiving combination prophylaxis [ 7 ]. When dosed correctly, HBIg is highly effective in maintaining adequate titers [ 14 , 15 ]. In the present cohort, 14.6% of patients had a serum anti-HBs level <100 IU/l, suggesting failure to maintain protective titers in this subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, there has been a significant shift in clinical trial management to allow for self-isolation, with remote trials becoming more commonplace [ 34 ]. Decentralised trials have been associated with increased patient empowerment and patient-centred care [ 35 ], and it has been suggested that the convenience of home administration may improve patient retention and compliance [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%